(untitled) (Research, Society and Development, 2024)
Objective: To conduct an integrative literature review to assess the role of Orlistat in inducing gastrointestinal inflammation, identify the underlying mechanisms, and provide a comprehensive overview of existing studies on the subject from 2019 to 2023. Method: Follows an integrative review approach, aiming to aggregate the results of published research and present them from a research question. Searches were conducted in various databases, including MEDLINE (via the PubMed portal of the National Library of Medicine), LILACS (Latin American and Caribbean Literature in Health Sciences), EMBASE, SCOPUS, and Web of Science. Results: 11 publications were selected for inclusion in the study. This relatively small number of included studies, compared to the initial number (195) of identified publications, reflects the rigor of the selection criteria and the emphasis on the quality and relevance of the data. Regarding the categories, Inflammation Biomarkers, Involved Mediators, Effects at Different Doses, and Impact of Treatment Duration were identified. Conclusion: It is concluded that the personalization of treatment, considering individual characteristics and patient response, is essential to maximize benefits and minimize adverse effects.